What's the Difference Between Front and Back Squats? - Volk, E.
Although they may seem identical, except for the bar placement, the front and back squat are two very different exercises that need to be understood to be beneficial. Squats are an excellent compound movement and considered the 'king' of lower body lifts. There are two major squat variations: the back squat and the front squat. While athletes and fitness individuals alike commonly use the back squat, the front squat is performed less. Although both effectively work the low back, hip and leg muscles, there are slight differences in technique and muscular involvement. The basic biomechanics of both squats are similar in that there is a starting position, descent and ascent. Each segment should be executed correctly to produce a strong, fluid, effective and safe squat movement. I'll address the back squat first and then briefly compare the front squat.